Role of innate immune cells in neurogenesis after spinal cord injury in zebrafish larvae - Drake, Louisa K. (The University of Edinburgh, 2023)
Unlike mammals, zebrafish can undergo complete functional recovery after spinal cord injury. One likely mechanism contributing to this regeneration is the proliferation and differentiation of ependymo-radial glial cells into new neurons. It is possible that some immune pathways are involved in re-initiating neurogenesis, as immune cells immediately infiltrate the site of spinal cord injury. Previously, global pharmacological manipulations of inflammation has shown that reducing inflammation results in lower levels of neurogenesis after central nervous system injury. However, the exact cell types and signals involved were still unknown. This project aimed to characterise the populations of immune cells and progenitor cells in the lesioned zebrafish and to identify potential pro-neurogenic signalling signals between the cell types. To identify any immune-derived signals at the lesion site, I performed single cell sequencing experiment on mpeg1+ progeny from both naïve and lesioned fish (24 hours post injury). Using marker genes, I identified the main subtypes of innate immune cells present at the lesion site including macrophages, microglia and neutrophils. Comparisons of the populations isolated from the naïve and lesioned fish revealed injury induced changes in these populations. I observed a notable expansion of the microglia cells in the lesioned fish compared to the unlesioned fish. Furthermore, I use changes in gene expression in the macrophages and microglia to deduce the injury induced changes undergone by these cells. Macrophages adopt an activated and secretory programme in the lesioned spinal cord. Similarly, single cell sequencing was performed on FAC sorted her4.3+ ependymo-radial glial cells and their progeny in the same injury conditions. Following unsupervised clustering, identities of the derived neuronal and glial clusters were assigned based on marker gene expression. Comparisons of these cell types before and after injury showed an expansion of a rare neuronal population with a putative neurosecretory function in the lesioned fish. Injury induced gene expression changes in our dataset were also compared to gene expression changes following injury in mice, to identify conserved and unique pathways across species. The transcription factor irf9 was upregulated in all mice progenitor populations after injury as well as our zebrafish dataset, indicating a conserved role in the injured spinal cord. Finally, the datasets were considered together in order to identify pathways of innate immune cell signalling to neuronal progenitor cells which may initiate promote neurogenesis. Receptor-ligand pairs were identified in which the ligands are up-regulated in the immune cells after injury and the corresponding receptors are present in the ependymo-radial glial cells. This identified some candidates for immune derived neurogenic pathways including Tnf signalling. Manipulating genes in the Tnf signalling cascade using CRISPR/Cas9 confirmed a pro-neurogenic function for immune-derived Tnf via its receptor on ependymo-radial glial cells. Overall, this research characterises the main immune and progenitor cell types involved in regenerative neurogenesis after spinal cord injury in zebrafish larvae. Comparing the cell populations before and after injury provides insight into the role of the immune system in promoting neurogenesis.
The role of innate immune cells in neurogenesis after spinal cord injury in zebrafish larvae
Keywords: Neurogenesis; spinal cord regeneration; zebrafish larvae; spinal cord injury